Threats Of The Covid-19 Pandemic On Existence Of Hospitality Business In Maintaining Business Continuity Management (BCM) - Lien Maulina; Sukmadi (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2021)
ABSTRACTThe spread of the corona virus (covid-19) is still a hot issue in the international world, including Indonesia. This outbreak has affected economic activity in Indonesia with a very significant impact, especially on one of the foreign exchange earners in Indonesia, namely the tourism sector. Ministry of Tourism and Creative Economy, the number of tourists coming to Indonesia is not only reduced but almost non-existent, including tourist visits to the hotel industry. All cross-sectoral and industrial organizations in dealing with the Covid-19 pandemic have made changes in their operations in business as usual conditions, where every activity in the workplace apart from their respective homes, both in offices, factories and other locations. Based on these problems, the purpose of this study is to identify and analyze the threat of the COVID-19 pandemic on the existence of the hospitality business in maintaining business continuity management (BCM). The research method used is a descriptive qualitative method based on secondary data in the form of journals related to research problems, research results and library references regarding data and information related to the threat of the covid 19 pandemic. Data collection techniques use documentation. Data analysis is done through content analysis. The results showed that the Covid-19 pandemic was an event in which the existence of the external environment was relatively uncontrollable or outside the company's control. The direct impact that affects business entities relates to conventional business activities in marketing, finance, human resources and operations. For hoteliers, it is necessary to adjust quickly in the midst of the Covid-19 pandemic and strive to develop product and service innovations in accordance with market demand trends accompanied by transformations in online application services as well as providing and displaying the applied health protocol and certification carried out by the Ministry of Tourism and Creative Economy.Keywords: Covid-19 Pandemic, Hospitality Business, Business Continuity Management (BMC)